POLYMORPHISM OF THE CYP2C19 ISOENZYME AS A RISK FACTOR FOR GASTROPATHIES INDUCED BY THE USE OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS IN PATIENTS WITH PAIN SYNDROME - Turdikul A. Bobomuratov; Abdukhakhor A.Samadov (Central Asian Journal of Medicine, 2022)
In the last decade, there has been a sharp increase in chronic kidney diseases (CKD) among children. In the US, Europe, Australia, Asian countries, it is noted that one-tenth of the world’s population suffers from a violation of kidney function. In 50% of patients with SBK, the disease is detected at the 3-5 stage of chronic renal failure (CRF), in 10% of patients at the terminal stage. At present, insufficient research has been conducted in the country to study the features and complications of kidney disease in children (Umarov R.Kh. 2010; Sharipov A.M. 2012; Khamzaev K.A., 2019; Rakhmonova L.K. 2020; Karimova U.N., 2020;).